Camera calibration with global LBP-coded phase-shifting wedge grating arrays. (January 2021) - Chen, Xiangcheng; Song, Xiaokai; Wu, Jun; Xiao, Yongxin; Wang, Yajun; Wang, Yuwei
Highlights: Phase-shifting wedge gratings (PWGs) with different periods form global coding on the target, each feature point has a unique corresponding label to identify its position, even when the targets are only partially captured. PWGs can ensure the accuracy of feature points extraction because of the invariable feature of lines intersections after projective transformation. Phase-shifting based feature detection method robust against to defocusing. Potential usage both in monocular and multi-camera calibration. Abstract: Non-contact optical measurement methods have been widely used in the fields of three-dimensional (3D) machine vision and photogrammetry attributed to their advantages of high precision, high speed and low cost. The calibration results directly affect the accuracy of the vision measurement system. Most of the existing calibration methods with two-dimensional (2D) targets need all of the feature points to be captured by the camera, otherwise it would be difficult to distinguish them due to the usage of identical feature points. This paper presents an active calibration target that consists of phase-shifting wedge gratings (PWGs) with three different periods and globally coded on the basis of rotation invariant local binary pattern (LBP) coding. Feature points are the intersections of several straight lines fitted by the 0 and π phase points. The sub-pixel coordinates can be accurately obtained with the phase-shifting method and the windowed linear fitting. Each feature point has its corresponding label to determine its specific position, therefore the one-to-one correspondence between the image coordinates and world coordinates can be obtained even the images are partially captured, and this characteristic can expand the flexibility in both monocular and multi-camera calibrations. In addition, owing to the phase-shifting method, calibration can be accomplished when the camera is defocused. Simulations and experiments further prove the flexibility and robustness of the proposed method.